Composição glicídica de alguns produtos dietéticos comercializados em Belo Horizonte - F Feitosa Teles, Francisco; E L Borges, Valéria; R Araújo, Joubert; A Moreira, Ademilde (Revista Ceres, 2025)
Forty products commercialized in Belo Horizonte, Brazil, as «dietetic» or as of low carbohydrate content were analyzed for digestible carbohydrates, total soluble carbohydrates, reducing sugars, non-reducing sugars and glucose content. After analysis of the results it was verified that some of these products had over 80% of digestible carbohydrates and six of them contained more than 20% of free glucose.